Tranexamic acid impairs plasmin generation on human mesenchymal stem cells and derived membrane microvesicles, halting pericellular proteolysis - Abou Rjeily, Ramy; Mrad, Christina; El-Ghazouani, Fatiha Z.; Toti, Florence; Cras, Audrey; Angles-Cano, Eduardo (Frontiers in Medicine, 2025)
IntroductionMesenchymal stem cells (MSCs) participate in the dynamic remodeling of the extracellular matrix during wound healing, natural bleeding processes or cancer progression. Pericellular proteolysis is a key mechanism mediating the aforementioned processes.AimThis study primarily aimed to define mechanistic pathways of plasmin formation and its consequences on MSC phenotype and functioning. We have also investigated the regulatory mechanisms mediated by PAI-1 and the ability of MSCs to shed microvesicles bearing the proteolytic machinery.MethodsHuman MSCs were derived from bone marrow or umbilical cord donors. Cells thus obtained were seeded in multi-well plates and treated with different concentrations of plasminogen and pro-urokinase in the presence or absence of variable amounts of tranexamic acid. We measured MVs formation and phenotypical changes occurring on MSCs. The amount of plasmin formed was quantified by western blot along with the plasmin activity detected by photometry.ResultsWe demonstrate that vesiculation is the early response of plasmin formation at the membrane of MSCs followed by cell retraction and detachment. We measured the effect of TXA on plasmin formation and its consequences on cell behavior. Our findings provide the first demonstration that TXA efficiently inhibits MSC-driven plasmin generation by competitively blocking plasminogen binding to the uPA•uPAR complex at the cell plasma membrane.DiscussionWe propose that plasmin formation on MSCs may be involved in pathological processes such as endometrial hemorrhage (metrorrhagia and Post-Partum Hemorrhage), autoimmune and ischaemic diseases, as well as cancer. By advancing our understanding of these mechanisms, we open new avenues for the development of biomarkers and targeted treatments.